CHANGE AT WINE MARKET IN THE COUNTRIES OF CEFTA REGION - Branislav Vlahović; Danilo Tomić; Anton Puškarić (Ekonomika Poljoprivrede (1979), 2011)
Viticulture and wine production are important industries in most of the countries who have signed CEFTA agreement. The countries of this region have favorable environmental conditions for a high production of grapes and wine. The subject and purpose of the research is to understand the trends of production, export and import in the countries of CEFTA region. Source of data is FAO database (Food and Agriculture Organization - FAO), for the time period 2000-2009. Average wine production in the given region is 610 million liters with a tendency of slight decrease at an average annual rate of 2.81%. Average wine export for countries of this group is the 243.5 million liters, with a tendency of slight decrease at a rate of 1.74%. Export price of wine is 0.9 dollars per liter, which indicates that lowerquality categories of wine (table wine) are mainly being exported. The most important exporter is Moldova with the participation of 63% of total exports from the region. Import of wine is 50 million liters with a trend of significant growth at an average rate of 12.44% per year. The largest importer is the Republic of Serbia with a share of 46.7% of the region. Countries in the region are achieving a positive trade balance of wine, averagely over 190 million liters. It is necessary to increase the production of wine with changes in the structure with regard to quality.